PERANAN PEMERINTAH DAN PARTISIPASI MASYARAKAT TERHADAP PENANGGULANGAN PERNIKAHAN DINI DI KECAMATAN PITU RIAWA KABUPATEN SIDENRENG RAPPANG - Herman Dema; Sarinah Sarinah (AkMen JURNAL ILMIAH, 2018)
The purpose of this research is to find out how the role of the Government against early marriage in penanggulanagn sub-district of Pitu Riawa, Sidenreng Rappang Regency to know how public participation against early marriage prevention in Sidenreng Rappang Regency Pitu Riawa, and to know the influence of early marriage is the driving factor in Sidenreng Rappang Regency Pitu Riawa. The population in this study is the Pitu Riawa sub-district who conducted an early marriage in 2016 that is as many as 40 people consisting of 12 men and 28 women. Sampling technique used in this study is Nonprobability sampling is a sampling technique that does not provide the same opportunity or opportunity for each element or member of the population to be selected to be sampled. Non-probability sampling technique used in sampling in this study more precisely the authors use saturated sampling technique. The definition of saturated sampling is a technique of determining the sample when all members of the population are used as a sample. So, the sample in this study is 40 people. The data collection techniques used are observation, questionnaire, interview, and Library Study (Library Research). The collected data is then analyzed by using likert scale and frequency table. The results of this study indicate that the role of government against early marriage management in District Pitu Riawa Sidenreng Rappang Regency with a value of 67.33% which means the role category. Community participation on early marriage management in Pitu Riawa District Sidenreng Rappang Regency with a value of 53.33%, which means the category is quite a role. And the influence of the factors driving the early marriage of Pitu Riawa Sub-district of Sidenreng Rappang Regency with 61,2% which means influential category.